(untitled) (Academicia Globe: Inderscience Research, 2021)
There is a saying that puts a huge responsibility on teachers’ shoulders: No any job in the world can exist without teachers. Responsibilities can be different for a teacher but the prime one is to be analytical when it comes to personal improvement. This small research is carried out to the practicality of some activities in real classroom. Initially, I set a number of goals ahead of me to do the task successfully and began taking notes after each lesson, according to the questions provided as prompts. After each lesson, I commenced to comprehend my own drawbacks in teaching. Each lesson, which was analyzed straightforwardly after having been conducted facilitated the second one to be more beneficial.